Analisis Pengaruh Upah Minimum Kabupaten/Kota (Umk), Indeks Pembangunan Manusia (IPM), Jumlah Penduduk Kabupaten/Kota, Dan Jumlah Penduduk Miskin Terhadap Tingkat Pengangguran Terbuka di Jawa Barat Tahun 2019-2023 - Suffah, Davina Aghnia Fella; Rahmi A, Aulia; Farida, Septiyani Nur; Naffriza S., Ghifarry Al; Faristanti, Nindya; Rahajeng, Anggi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study analyzes the influence of the minimum wage (UMK), Human Development Index (HDI), total population, and the number of poor people on the Open Unemployment Rate (TPT) in West Java during the 2019–2023 period using panel data regression with the Random Effect Model. The results show that UMK and the number of poor people have a significant positive effect on TPT, while HDI and total population have a significant negative effect. The study recommends improving human development quality and managing minimum wages effectively to reduce the unemployment rate.